(3GdfcJ Ydi GdCdajI hGdcGajI hGdTGajI hTPhQ GdPgH hfRgI GdWQas - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3SdjeGf Hf Ydj Hf MSf GdHMjQj GdeGdcj s)
(3ChdgG (B:s
(3CeG HYO GdMeO ddg Ydi fYeI GdcGajI heffg GdTGajI agPg fcJ MQQJgG Ydi cJH aj Yde GdYQHjI s
(3BNQgG (B:s
(3adeG cGf aj QeVGf SfI NeS hJSYjf TQM Gddg UOQj dEceGdg, aCNPJ aj Pdc, hGfJgi aQGZg Je hced s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B335 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1977s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs